PROFITABILITAS, LEVERAGE, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DIMODERASI KEBIJAKAN DEVIDEN - Aziz, Ahmad Nur; Sari, Erma Wulan (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2021)
The purpose of this study is to determine the effect of profitability, leverage and liquidity on the value of companies with dividend policies as moderate variables in LQ45 indexed companies in 2014-2018. This type of research is quantitative with purposive sampling techniques. The sample results obtained are 7 companies with historical data of 5 years. Analysis techniques using linear regression analysis and MRA. The results of this study show that profitability, leverage and liquidity simultaneously and in part have a positive effect on the value of the company. dividend policy is not able to moderate the effect of profitability on the value of the company but is able to moderate by strengthening the influence of leverage and liquidity on the value of the company